Pengaruh E-WoM, Promotion dan Place Terhadap Customer Satisfaction PT POS Indonesia (Persero) Kota Probolinggo - Prycylya Putri Amalia; Rr Setyani Hidayati; Dedi Joko Hermawan (Universitas Panca Marga, 2024)
The purpose of this study was to determine the effect of E-WoM, Promotion, and Place on Customer Satisfaction PT. Pos Indonesia (Persero) Probolinggo City. Customers in June 2023 are the population of this study. The data collection method used non-probability sampling, and obtained 99 respondents and a linear regression analysis tool using the SPSS 26 application. The ways of collecting information carried out in this study were: Questionnaire, observation and documentation. The results of the E-WoM have a partial effect on Customer Satisfaction. Promotion have a partial effect on Customer Satisfaction. Place tests have a partial effect on Customer Satisfaction.